ANALISIS PENERAPAN E-GOVERNMENT PADA PEMERINTAH DAERAH PROVINSI SULAWESI TENGAH - Sonny, Sonny (Katalogis, 2013)
AbstractÂ This research aimed at finding out and analyzing the e-Goverment of Central Sulawesi Province and to what extent the e-government has been implemented. This research used descriptive method employing qualitative approach. The informants were taken purposively, which means that they understood well about the subject matter and those who got involved in the e-goverment. The technique used was qualitative data analysis in which the researcherâ€™s own reasoning for connectin facts, data, and information was used. In this research, implementation of E-Government in Central Sulawesi Province Government has not run optimally and effectively, because it is not supported by the quality and capacity of Human Resources (Human Resource Skills) consequently less data is valid and up to date. In addition, the Internet network running optimally in accessing data from outside because it is not supported by device policy for the Governor of Central Sulawesi. Financing e-government in the province of Central Sulawesi done in stages in accordance with what has been planned to the area 2011-2016.